Reproductive Endocrine Mechanisms Regulating Ovarian Reserve in Polyendocrine Metabolic Ovarian Syndrome - Yixin Feng (International Journal of Public Health and Medical Research, 2026)
This paper investigates the reproductive endocrine mechanisms of the ovarian reserve in polyendocrinopathy, autoimmune polyglandular syndrome type 1 (APCOS), which is a new term for polycystic ovary syndrome (PCOS). Rather than viewing ovarian reserve as a single number, the paper believes that the concept of reserve in PMOs should be understood through the interplay of follicle number, follicular arrest, granulosa-cell signalling, gonadotropin imbalance, androgen excess and metabolic disturbances. Based on the major consensus statements and endocrine studies, this essay will explore how disturbed hypothalamic-pituitary-ovarian signalling, functional ovarian hyperandrogenism, insulin-related dysregulation and anti-Mullerian hormone overproduction affect folliculogenesis and complicate the interpretation of ovarian reserve markers. PMOS also has a problem: although it appears to be in an overstocked state, it may not be ready to reproduce normally. Therefore, Ovarian Reserve Markers in PMOS should be considered in the context of the whole-body endocrine environment and not regarded as fixed indicators of ovulation potential.